2005
DOI: 10.1099/ijs.0.63553-0
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Mycobacterium species by analysis of the heat-shock protein 65 gene (hsp65)

Abstract: The nucleotide sequences (604 bp) of partial heat-shock protein genes (hsp65) from 161 Mycobacterium strains containing 56 reference Mycobacterium species and 105 clinical isolates were determined and compared. hsp65 sequence analysis showed a higher degree of divergence between Mycobacterium species than did 16S rRNA gene analysis. Generally, the topology of the phylogenetic tree based on the hsp65 DNA sequences was similar to that of the 16S rRNA gene, thus revealing natural relationships among Mycobacterium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
156
1
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(165 citation statements)
references
References 33 publications
5
156
1
3
Order By: Relevance
“…Studies have shown that the level of sequence similarity between isolates in a given species is >98.2% with some species like MTB showing 100% similarity in all isolates. 12 Phylogenetic analysis using this sequence has shown great similarity to the phylogenetic tree generated from 16S rRNA analysis. 12 Hsp65 sequencing has been shown to have a greater resolving ability than 16S rRNA sequencing as well.…”
Section: Results Dna Extractionmentioning
confidence: 79%
See 1 more Smart Citation
“…Studies have shown that the level of sequence similarity between isolates in a given species is >98.2% with some species like MTB showing 100% similarity in all isolates. 12 Phylogenetic analysis using this sequence has shown great similarity to the phylogenetic tree generated from 16S rRNA analysis. 12 Hsp65 sequencing has been shown to have a greater resolving ability than 16S rRNA sequencing as well.…”
Section: Results Dna Extractionmentioning
confidence: 79%
“…2,3 Hsp65 restriction digestion with BstEII and HaeIII enzymes has been used extensively for NTM identification in multiple fields of study, while gyrB digestion with RsaI and TaqIhas been successfully used for M. tuberculosis (MTB) /M.africanum differentiation from M.bovis/ BCG. [4][5][6][7][8][9][10][11][12][13] In Sri Lanka, NTM were cultured in approximately 2-3% of all mycobacterial cultures done at the National Tuberculosis Reference Laboratory between 2005 and 2007 14,15 while a recent analysis of bronchoscopy cultures from patients in Kandy by Weeresekera et al showed that -13-14 % were positive for NTM isolates, including M.phocaicumand M. Smegmatis. 16 Data on the true (overall) NTM infection rate among patients with pulmonary and extra pulmonary disease in Sri Lanka is not available as cultures are not routinely performed in suspected pulmonary tuberculosis.…”
Section: Introductionmentioning
confidence: 99%
“…The following three fragments were amplified: (1) the 644 bp fragment of the hsp65 gene encoding the heat-shock protein (Kim et al, 2005), (2) a 353 bp fragment of the gyrB gene encoding the DNA gyrase B and (3) a 933 bp fragment of the rpsA gene encoding the ribosomal protein S1. We then designed primers in order to amplify the gyrB and rpsA genes.…”
Section: Methodsmentioning
confidence: 99%
“…Fast and accurate molecular approaches for the identification and differentiation of MAC members are therefore needed in order to assess the pathogenicity of MAC subspecies and to provide routine diagnostic tools for the clinician. The partial hsp65 gene has been proposed by Kim et al (2005) as a useful target molecule for the identification and phylogenetic analysis of Mycobacterium species. In the case of our isolate, however, the nucleotide sequence of the hsp65 gene perfectly matched both the M. avium subsp.…”
Section: F Armas and Othersmentioning
confidence: 99%
“…Extraction of mycobacteria and sputum DNAs, and PCR conditions and primer set to amplify the 644 bp hsp65 DNAs were performed as described previously (12,13). M. tuberculosis IS6110 DNAs (536 bp) (18) were separately amplified using an IS6110 kit.…”
mentioning
confidence: 99%